Association of the systemic immune-inflammation index with all-cause mortality in patients with arteriosclerotic cardiovascular disease - He, Lu; Xie, Xuegang; Xue, Jianying; Xie, Hang; Zhang, Yushun (Frontiers in Cardiovascular Medicine, 2022)
Objective: Systemic immune-inflammation index (SII), derived from blood cell counts of circulating platelets, neutrophils and lymphocytes, has been identified as a novel inflammatory and prognostic marker. However, the clinical value of SII in patients with arteriosclerotic cardiovascular disease (ASCVD) had not been further explored. Thus, this study designs to explore the associations of SII with mortality in ASCVD individuals. Methods: All individuals with ASCVD aged ≥20 years were included from the National Health and Nutritional Examination Surveys (NHANES) 2005–2014, and followed for survival until December 31, 2019. Multivariable Cox analysis investigated the associations between SII, evaluated as a continuous variable with splines and as categorical ones (quartiles), and the all-cause death. To demonstrate the association between SII and mortality, subgroup analysis, restricted cubic spline along with piecewise linear regression were also conducted. Results: A total of 2595 participants (57.8% men) were included. During a median of 7.7 years follow-up, 1122 deaths due to all-cause were recorded. After adjusting for multiple confounders, compared with the patients in quartile 1 (SII ln transform), those in quartile 4 had 46% increased risk for all-cause death (HR = 1.46, 95%CI = 1.22-1.75). As a continuous variable, each unit of raised ln-SII was associated with 24% increased risk of all-cause death (HR = 1.24, 95%CI = 1.10-1.38). In the restricted cubic spline regression model, the relationship between ln-SII and all-cause death was non-linear. The cut-off value of ln-SII for mortality was 6.57 and those with higher than the threshold point had 1.25-fold risk of mortality. No significant difference was noted below the threshold points. Conclusion: A association was detected between the baseline ln-SII and all-cause mortality in a US ASCVD population. Elevated SII is associated with poor survival in individuals with ASCVD